Identification of Creative Thinking Ability in Online Learning of Lower Group Students by Using the Treffinger Method - Astrid Chandra Sari; Festian Cindarbumi; Hana Istiqomah (Urogram Studi Pendidikan Matematika, Universitas IVET, 2022)
Two factors that cause creative thinking does not develop during education are the curriculum and educators, which are generally designed with a broad target, so that educators focus more on completing the material. In this case, it is known that mathematics learning that has occurred so far has not been able to attract students' attention, especially in creative thinking. This study aims to improve students' creative thinking skills with the Treffinger learning model. This study uses a mixed method (a combination of quantitative and qualitative methods). This research was conducted in class VII MTs SA Al Istiqomah on the material of triangular and quadrilateral shapes. These students of MTs Sa Al Istiqomah Mojosari class VII total of 15 students. The research sample amounted to 2 students who were selected using a sampling technique. In addition, one student with high post-test or high scores (SNT) and one low-scoring student (SNR) will be interviewed. The indicators of creative thinking used in this study are indicators (1) Fluent, (2) Flexible, (3) Original, and (4) Detailed. The results showed that students with low scores and high scores overall were included in the category of students with high creative thinking abilities because more than 85% of students met the criteria for high creative thinking abilities. This was evidenced by the fulfillment of all indicators of creative thinking abilities. However, there are still some students whose scores are below the average. This is evidenced by students only being fluent and flexible, which means that the original and detailed indicators have not been met. Keywords: Creative Thinking, Two Dimensional Figure, Treffinger.